Fertility and the size of the U.S. labor force. - Olsen, Randall J. (Journal of Economic Literature, 1994)
This paper reviews and interprets from an economic perspective the demographic trends in the U.S. since the turn of the century. The primary focus will be upon the interplay between the fertility and labor force participation of women and how they may be interpreted within simple economic models....We will begin by stating what economic demography is and why careful analytic methods are needed. Section II provides a brief demographic history of the U.S. Section III describes the major economic theories of fertility and Section IV discusses the empirical performance of these theories. Section V discusses the linkages between fertility and the size of the labor force and Section VI concludes. (EXCERPT)